Characterisation of mycoflora and aflatoxigenic fungi from portuguese almonds: from production to commercialization - Rodrigues, Paula (2009)
Introduction: Aflatoxins are  among  the  most  carcinogenic  natural  compounds known, and have been frequently detected in numerous agricultural commodities, nut fruits being among the most contaminated ones. These toxins are a  result of the secondary metabolism of fungi belonging to  the genus Aspergillus Section Flavi, namelly Aspergillus flavus, A. parasiticusand A. nomius. The early detection of aflatoxigenic fungal contamination and the  preventive control of aflatoxin production seems to be the only  viable  way  to  respond  to  the  rigorous  limits  imposed  by  EU  legislation.  In  Portugal,  knowledge  on  mycoflora and  mycotoxigenic profiles of almonds is scarce. Our objective was to characterise portuguese almonds in respect to mycoflora, with  strong  emphasis  on  aflatoxigenic fungi,  from  production to commercialization.